DEMONSTRATION OF EFFECTIVENESS OF IMPLEMENTATION METHOD OF STUDENT LEARNING PRAYERS - Amirudin Amirudin; Iqbal Amar Muzaki (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2021)
This study aims to determine the application, supporting and inhibiting factors and results achieved. The research method used was descriptive, with research subjects were students of SDN Karawang Wetan Kab. Karawang. The research technique used was Simple Random Sampling, techniquewhile the data collection technique was carried out through observation, literature study, and a questionnaire distributed to 45 respondents as a sample in this study. The results of the study concluded that the effectiveness of the implementation of the demonstration method in the implementation of the Prayer Service for students of Karawang Wetan Elementary School was said to be quite successful with a number of 71.7%.